Spatial patterns and its influencing factors on villages around the Ji-shape bend of the Yellow River - Wang, Zhiqiang; Jiang, Shuang; Xu, Shuang; Zhang, Jianxun; Mumtaz, Faisal; Zhang, Maomao (Frontiers in Environmental Science, 2024)
The Ji（几）-shape bend of the Yellow River is of important ecological value, with diverse geographic and cultural settings. Influenced by documents and policies, as well as the unique topography of the region, Inner Mongolia was chosen as the research object. Existing research has mostly focused on the single dimension, but this article conducts research from multiple dimensions. The differentiated development ideas of the villages were discussed and their overall distribution pattern was determined, in terms of the characteristics of the Ji-shape bend of the Yellow River. This article mainly used the research method of Arc GIS10.8, the big data research methods such as imbalance index, Gini coefficient, geographic concentration index, Geodetector, and other methods were used, laying the groundwork for additional analysis of various factors. Hence, the subsequent study findings were attained. (1) The distribution pattern in the village system around the Ji-shape bend of the Yellow River seems to be a positive spatial correlation, with the characteristics of random distribution, uneven spatial distribution, and low concentration, with Hohhot-Baotou serving as a center. (2) Natural factors are the most important factors in the distribution of villages. (3) Among the natural factors, elevation (0.244619), the value of slope (0.319805), and the aspect of slope (0.074089) appear to be the strongest explanatory power. Among the social factors, the rate of urbanization (0.019082), highway density (0.019082), and percentage of tertiary industry (0.018422) show the strongest explanatory power on socioeconomic factors. Ultimately, it was proposed that the importance of climate change should be emphasized to preserve and promote village growth, and ecological construction should be included in the villages located on the river basin, as well as protection measures. The article may serve as a reference for the subsequent village construction and development.